2022
DOI: 10.3389/fneur.2022.1017982
|View full text |Cite
|
Sign up to set email alerts
|

Association of Obstructive Sleep Apnea-Hypopnea Syndrome with hearing loss: A systematic review and meta-analysis

Abstract: ObjectiveThis study seeks to investigate the relationship between Obstructive Sleep Apnea-Hypopnea Syndrome (OSAHS) and hearing impairment by meta-analysis.MethodsCochrane Library, PubMed, Embase, Web of Science and other databases are searched from their establishment to July 1st, 2022. Literature on the relationship between OSAHS and hearing loss is collected, and two researchers independently perform screening, data extraction and quality evaluation on the included literature. Meta-analysis is performed usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…Results show consistency. It is widely confirmed in the existing literature that ambient noise, OSAH and snoring are independent risk factors of HL, which the CHARLS dataset did not record ( 41 , 42 , 68 70 ). However, even after controlling for noise exposure, the association between short sleep duration and HL remained significant ( 71 ).…”
Section: Discussionmentioning
confidence: 69%
“…Results show consistency. It is widely confirmed in the existing literature that ambient noise, OSAH and snoring are independent risk factors of HL, which the CHARLS dataset did not record ( 41 , 42 , 68 70 ). However, even after controlling for noise exposure, the association between short sleep duration and HL remained significant ( 71 ).…”
Section: Discussionmentioning
confidence: 69%
“…[21] A recent meta-analysis reported that 4 and 8 kHz hearing thresholds of the OSA patients were significantly higher than those of the control group, and snoring might have caused hearing impairment in those patients. [8] Similarly, Chopra et al reported that presence of OSA was significantly correlated with hearing impairment, and both presence of OSA and increased OSA severity were correlated with increased likelihood of hearing impairment in both high and low frequencies. [7] Seo et al indicated that lowest oxygen saturation was the only variable correlated with hearing thresholds, and severe OSA might be a trigger for hearing loss.…”
Section: Discussionmentioning
confidence: 95%
“…[18] Moreover, cochlear and brainstem microcirculations may be impaired due to autonomic nervous system dysfunction, hypoxia and inflammation, resulting in hearing impairment. [8] Hearing loss may also lead to tinnitus. [19] Vorlova et al investigated the effect OSA on hearing, and reported that OSA resulted in hearing impairment possibly due to hypoxia, heart rate variations, decreased brain perfusion and changes in intracranial pressure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, there has been emerging evidence indicating the association between sleep disorders and hearing loss 18 . Patients with a diagnosis of OSA were found to have higher rates of audiometry‐measured hearing loss based on population‐based and clinic‐based cohorts 19‐22 .…”
mentioning
confidence: 99%